The Kirkendall effect towards oxynitride nanotubes with improved visible light driven conversion of CO2 into CH4. Issue 8 (22nd January 2016) - Zhou, P.; Gao, H. L.; Yan, S. C.; Zou, Z. G.
Abstract : ZnGaNO nanotubes can be obtained via the Kirkendall effect, exhibiting the high photocatalytic performance due to the short carrier diffusion distance and less crystal defects. Abstract : Functional hollow nanomaterials are of great interest due to their unique physical–chemical properties. Oxynitride photocatalysts are a kind of promising material for solar energy conversion. However, nanoscale design of hollow oxynitrides was difficult to achieve due to the thermal instability of oxide precursors at high temperature. Here, single crystal zinc gallium oxynitride nanotubes were successfully synthesized via the Kirkendall effect with ZnO nanorods and Ga2 O3 nanosheets as precursors, which can be attributed to the high diffusion rate of ZnO and the high melting point of oxynitride. Enhanced photocatalytic performance in CO2 reduction was achieved over the as-prepared ZnGaNO nanotubes, due to their higher specific surface area and less recombination of the photogenerated carriers. These results are expected to provide new guidance in the design and preparation of highly efficient nano-scaled oxynitride photocatalysts.